1998
DOI: 10.1063/1.122786
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric effects on the optical properties of GaN/AlxGa1−xN multiple quantum wells

Abstract: Abstract:Piezoelectric effects on the optical properties of GaN/AlGaN multiple quantum wells (MQWs) have been investigated by picosecond time-resolved photoluminescence (PL) measurements. For MQWs with well thickness 30 A and 40 A, the excitonic transition peak positions at 10 K in continuous wave (cw) spectra are redshifted with respect to the GaN epilayer by 17 meV and 57 meV, respectively. The time-resolved PL spectra of the 30 A and 40 A well MQWs reveal that the excitonic transition is in fact blueshifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 15 publications
0
74
0
Order By: Relevance
“…It has been found that coherently strained Al 0.25 Ga .075 N can be grown up to ϳ300 A on GaN. 15 This indicates that strain relaxation should not cause a significant shift from these calculated Schottky heights. Doping density is found to have a significant effect on the effective Schottky height.…”
Section: Schottky Detectorsmentioning
confidence: 69%
“…It has been found that coherently strained Al 0.25 Ga .075 N can be grown up to ϳ300 A on GaN. 15 This indicates that strain relaxation should not cause a significant shift from these calculated Schottky heights. Doping density is found to have a significant effect on the effective Schottky height.…”
Section: Schottky Detectorsmentioning
confidence: 69%
“…Currently there are no measured data available on the interface roughness characteristics, to the best of our knowledge. In the absence of such data, the interface roughness correlation length L, and the rms height of interface roughness fluctuations ), 33 were taken as adjustable parameters. It was implicitly assumed that the interface roughness process could be adequately modeled in the Born approximation with the use of weak-perturbation theory, and that localization effects were negligible.…”
Section: D2 Monte Carlo Results For Hemtsmentioning
confidence: 99%
“…From this the piezoelectric field strength can also be estimated. By comparing experimental and calculation results, a lower limit value of the piezoelectric field strength of about 560 kV/cm in GaN/Al 0.15 Ga 0.85 N MQWs as well as the electron and hole wave functions have been obtained for a 40 Å well MQW [8].…”
Section: Time-resolved Pl Spectramentioning
confidence: 99%
“…Recent work on the III-nitride alloy systems and MQWs has shown that localized excitons dominate the optical transitions in these systems at low temperatures [2][3][4]. And, it has been proposed and shown that piezoelectric fields due to lattice mismatch-induced strain in InGaN/GaN MQWs [5,6] and GaN/AlGaN QWs [6][7][8][9] are the primary reason for the large redshift of the photoluminescence (PL) emission peak. Indeed the piezoelectric field in strained layers has been used to modify the operating characteristics of devices fabricated from these materials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%